Network, personality and social capital - Venkatanathan, Jayant; Karapanos, Evangelos; Kostakos, Vassilis; Gonçalves, Jorge (My University, 2012)
We present a study on the relationship between social network structure on Facebook and social capital, and how this relationship is moderated by personality traits. The findings suggest that one's number of friends does not necessarily have an effect on the amount of bridging social capital. Conversely, the extent of structural holes and isolated friends in the network have an effect on bridging social capital. In addition, individuals low on agreeableness benefit more from isolated friends in terms of bridging social capital. In terms of bonding social capital, introverts benefit more from networks with higher transitivity. Women overall report higher bonding social capital, but there are no significant gender differences when it comes to leveraging one's network structure for bridging or bonding social capital.
Keywords: Ego networks; Personality traits; Social capital; Social networks analysis